Magnetic component

The proposed magnetic component structure, with a thin Fe oxide layer and a thicker Si oxide layer on magnetic particles, enhances permeability and saturation magnetic flux while maintaining insulating properties, addressing the challenges of miniaturization and thinning in magnetic components.

JP2025063833APending Publication Date: 2025-04-16SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024157203
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-04
Filing Date
2024-09-11
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

The challenge is to enhance the permeability, saturation magnetic flux value, and overall magnetic properties of miniaturized and thinned magnetic components while maintaining adequate insulating properties to prevent eddy current losses.

Method used

A novel magnetic component structure is proposed, featuring magnetic particles with a thin Fe oxide layer (less than 5 nm) and a thicker Si oxide layer (5 nm or more), which improves magnetic permeability and insulating properties without compromising saturation magnetic flux characteristics.

Benefits of technology

This configuration achieves high magnetic permeability and saturation magnetic flux characteristics while maintaining excellent insulating properties, effectively addressing the limitations of existing miniaturized magnetic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063833000001_ABST
    Figure 2025063833000001_ABST
Patent Text Reader

Abstract

To achieve a surface insulating layer of a magnetic particle having a reduced thickness and excellent magnetic characteristics, to improve the magnetic permeability and saturation magnetic flux density value of a magnetic component.SOLUTION: According to an embodiment of the present invention, a magnetic member including a magnetic substance is provided. The magnetic substance includes a plurality of magnetic particles including a Fe-based alloy component. At least part of the plurality of magnetic particles includes a first layer formed on a surface and a second layer formed on a surface of the first layer. The first layer includes a Fe oxide component and has an average thickness of less than 5 nm. The second layer includes a Si oxide component and has an average thickness of 5 nm or more.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a magnetic component. [Background technology]

[0002] As electronic devices such as digital TVs, mobile phones, and laptops become smaller and thinner, the magnetic components used in these devices are also required to be smaller and thinner, and various types of magnetic components are being used to meet this demand. An example of a magnetic component is an inductor, which includes a coil, and research and development into wire-wound and thin-film inductors is currently underway.

[0003] The main issue with miniaturizing and thinning magnetic components is maintaining the same performance as existing products. To meet this demand, the proportion of magnetic material in the core must be increased, but there are limitations to increasing the proportion due to factors such as changes in frequency characteristics due to the strength and insulating properties of the magnetic material.

[0004] One method for manufacturing magnetic components involves laminating a sheet containing a mixture of magnetic particles and resin onto a coil, then applying pressure to form the main body. Ferrite or metal can be used as the magnetic particles. When using metal magnetic particles, it is advantageous to increase the particle content in terms of the magnetic permeability characteristics of the magnetic component. However, this can reduce the insulating properties of the magnetic material and cause eddy current loss. Furthermore, coating the surfaces of the metal magnetic particles with an insulating layer reduces the proportion of the metal magnetic particles in the magnetic material, potentially adversely affecting the magnetic properties. Summary of the Invention [Problem to be solved by the invention]

[0005] One of the objects of the present invention is to improve the magnetic permeability, saturation magnetic flux value, etc. of a magnetic part by realizing a surface insulating layer of magnetic particles that is thin and has excellent magnetic properties. [Means for solving the problem]

[0006] As a method for solving the above-mentioned problems, the present invention proposes, through one example, a novel structure of a magnetic component, specifically, a magnetic component including a magnetic body, the magnetic body including a plurality of magnetic particles including an Fe-based alloy component, at least some of the plurality of magnetic particles including a first layer formed on the surface and a second layer formed on the surface of the first layer, the first layer including an Fe oxide component and having an average thickness of less than 5 nm, and the second layer including a Si oxide component and having an average thickness of 5 nm or more.

[0007] In one embodiment, the first layer may contain less than 1 wt % of Si.

[0008] In one embodiment, the second layer may contain 30% to 70% by weight of a Si component.

[0009] In one embodiment, the average thickness of the second layer can be less than 50 nm.

[0010] In one embodiment, the average thickness of the second layer may be 2 to 10 times the average thickness of the first layer.

[0011] In one embodiment, the magnetic particles may have an average diameter of 10 to 25 μm.

[0012] In one embodiment, the at least some of the magnetic particles may further include a third layer formed on the surface of the second layer.

[0013] In one embodiment, the third layer can include at least one functional group selected from the group consisting of an alkyl group, a carbonyl group, and a urethane acrylate.

[0014] In one embodiment, the magnetic material may include at least one component selected from the group consisting of oleic acid, a derivative of oleic acid, and carbonic acid monoamide n-allyl neopentyl ester.

[0015] In one embodiment, the average thickness of the third layer can be less than 10 nm.

[0016] In one embodiment, the Fe-based alloy may include an Fe—Si—BC-based material.

[0017] In one embodiment, the Fe-based alloy may be free of Cr, Mo, Nb, and P elements.

[0018] In one embodiment, in the Fe-based alloy, the content of Fe can be more than 90 wt%.

[0019] In one embodiment, the Si content in the Fe-based alloy may be 0.1 to 5 wt %.

[0020] In one embodiment, the magnetic body may further include additional magnetic particles having an average diameter smaller than the magnetic particles comprising the first and second layers.

[0021] In one embodiment, the additional magnetic particles may include carbonyl iron powder. [Effects of the Invention]

[0022] A magnetic component according to an example of the present invention can have excellent magnetic properties, such as high levels of magnetic permeability and saturation magnetic flux characteristics. [Brief explanation of the drawings]

[0023] [Figure 1] 1 is a schematic transparent perspective view showing a magnetic component according to an embodiment of the present invention; [Figure 2]2 is a cross-sectional view of a region of the magnetic component of FIG. 1. [Figure 3] 2 is an enlarged view of one region of the magnetic material in the magnetic component of FIG. 1. [Figure 4] This shows how the thickness of the surface insulating layer of the magnetic particles decreases. [Figure 5] 10 illustrates magnetic particles that may be employed in a modified magnetic component. [Figure 6] 10 is an enlarged view of one region of a magnetic body of a magnetic component according to a modified example. [Figure 7] FIG. 10 is a schematic transparent perspective view showing a magnetic component according to another embodiment of the present invention. [Figure 8] FIG. 8 is a schematic exploded perspective view of the magnetic component of FIG. 7. [Figure 9] 8 is a cross-sectional view of a region of the magnetic component of FIG. 7. DETAILED DESCRIPTION OF THE INVENTION

[0024] Hereinafter, embodiments of the present invention will be described with reference to specific embodiments and the accompanying drawings. However, the embodiments of the present invention can be modified into several other forms, and the scope of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those skilled in the art. Therefore, the shapes and sizes of elements in the drawings may be enlarged or reduced (or highlighted or simplified) for clearer explanation, and elements designated by the same reference numerals in the drawings are the same elements.

[0025] Various types of electronic components are used in electronic devices, and various types of magnetic components can be appropriately used between these electronic components for the purpose of noise removal, etc. That is, in electronic devices, magnetic components can be used as power inductors, high frequency inductors, general beads, high frequency beads (GHz beads), common mode filters, etc.

[0026] FIG. 1 is a schematic perspective view showing a magnetic component according to one embodiment of the present invention, FIG. 2 is a cross-sectional view of a region of the magnetic component of FIG. 1, and FIG. 3 is an enlarged view of a region of the magnetic material in the magnetic component of FIG. 1.

[0027] 1 to 3, a magnetic component 100 according to this embodiment includes a magnetic body 101 including a plurality of magnetic grains 111. At least some of the magnetic grains 111 include a first layer 112 formed on the surface and a second layer 113 formed on the surface of the first layer 112. The first layer 112 contains an Fe oxide component and has an average thickness t1 of less than 5 nm. The second layer 113 contains a Si oxide component and has an average thickness t2 of 5 nm or more. This coating structure reduces the volume fraction of the Fe oxide layer within the magnetic grains 111, thereby minimizing the degradation of the magnetic permeability characteristics of the magnetic grains 111 and further improving the insulating characteristics of the magnetic grains 111. The main components of the magnetic component 100 according to this embodiment are described below.

[0028] The magnetic body 101 has the appearance of a magnetic component 100, and may include a coil 103 and a support member 102 for supporting the coil 103. As shown in FIG. 3, the magnetic particles 111 may be dispersed within an insulating material 110. The insulating material 110 may include a dispersant, a binder, etc., and may include a polymer component such as epoxy resin or polyimide. The magnetic body 101 may be formed in a hexahedral shape as a whole. For example, the magnetic body 101 may be formed so that the magnetic component 100 according to this embodiment, including the external electrodes 105 and 106, has a length of 2.5 mm, a width of 2.0 mm, and a thickness of 1.0 mm, a length of 2.0 mm, a width of 1.2 mm, and a thickness of 0.65 mm, a length of 1.6 mm, a width of 0.8 mm, and a thickness of 0.8 mm, a length of 1.0 mm, a width of 0.5 mm, and a thickness of 0.5 mm, or a length of 0.8 mm, a width of 0.4 mm, and a thickness of 0.65 mm, but is not limited thereto. However, the above numerical values ​​are merely design values ​​that do not reflect process errors, and therefore, any range that can be considered as process errors should be considered within the scope of the present invention.

[0029] The length of the magnetic component 100 in the first direction D1 may refer to, based on an optical microscope or SEM (Scanning Electron Microscope) photograph of a cross-section of the magnetic component 100 in the first direction D1-third direction D3 at the center of the second direction D2 of the magnetic component 100, the maximum dimension of each of a plurality of line segments parallel to the first direction D1 when connecting two outermost boundary lines of the magnetic component 100 facing the first direction D1 shown in the cross-section photograph. Alternatively, the length may refer to the minimum dimension of each of a plurality of line segments parallel to the first direction D1 when connecting two outermost boundary lines of the magnetic component 100 facing the first direction D1 shown in the cross-section photograph. Alternatively, the length may refer to the arithmetic mean value of at least three or more dimensions of a plurality of line segments parallel to the first direction D1 when connecting two outermost boundary lines of the magnetic component 100 facing the first direction D1 shown in the cross-section photograph. Here, the plurality of line segments parallel to the first direction D1 may be equally spaced from one another in the third direction D3, but the scope of the present invention is not limited thereto.

[0030] The length in the second direction D2 of the magnetic component 100 may refer to, based on an optical microscope or SEM (Scanning Electron Microscope) photograph of a cross-section of the magnetic component 100 in the first direction D1-second direction D2 at the center of the third direction D3 of the magnetic component 100, the maximum dimension of each of a plurality of line segments parallel to the second direction D2, obtained by connecting two outermost boundary lines of the magnetic component 100 facing the second direction D2 shown in the cross-section photograph. Alternatively, the length in the second direction D2 may refer to the minimum dimension of each of a plurality of line segments parallel to the second direction D2, obtained by connecting two outermost boundary lines of the magnetic component 100 facing the second direction D2 shown in the cross-section photograph. Alternatively, the length in the second direction D2 may refer to the arithmetic mean value of at least three or more dimensions of a plurality of line segments parallel to the second direction D2, obtained by connecting two outermost boundary lines of the magnetic component 100 facing the second direction D2 shown in the cross-section photograph. Here, the plurality of line segments parallel to the second direction D2 may be equally spaced from one another in the first direction D1, but the scope of the present invention is not limited thereto.

[0031] The length of the magnetic component 100 in the third direction D3 may refer to, based on an optical microscope or scanning electron microscope (SEM) photograph of a cross-section of the magnetic component 100 in the first direction D1-third direction D3 at the center of the second direction D2 of the magnetic component 100, the maximum dimension of each of a plurality of line segments parallel to the third direction D3, obtained by connecting two outermost boundary lines of the magnetic component 100 facing the third direction D3 shown in the cross-section photograph. Alternatively, the length may refer to the minimum dimension of each of a plurality of line segments parallel to the third direction D3, obtained by connecting two outermost boundary lines of the magnetic component 100 facing the third direction D3 shown in the cross-section photograph. Alternatively, the length may refer to the arithmetic mean value of at least three of the dimensions of a plurality of line segments parallel to the third direction D3, obtained by connecting two outermost boundary lines of the magnetic component 100 facing the third direction D3 shown in the cross-section photograph. Here, the plurality of line segments parallel to the third direction D3 may be equally spaced from one another in the first direction D1, but the scope of the present invention is not limited thereto.

[0032] Meanwhile, the lengths of the magnetic component 100 in the first to third directions D1-D3 can also be measured by a micrometer measurement method. The micrometer measurement method can be performed by setting a zero point with a micrometer with Gauge R&R (Repeatability and Reproducibility), inserting the magnetic component 100 according to the present embodiment between the tips of the micrometer, and turning the measuring lever of the micrometer. Meanwhile, when measuring the length of the magnetic component 100 by the micrometer measurement method, the length of the magnetic component 100 can refer to a value measured once or an arithmetic average of values ​​measured multiple times.

[0033] Referring to FIG. 3, the magnetic body 101 includes a plurality of magnetic grains 111 containing an Fe-based alloy component. When the magnetic grains 111 are made of an Fe-based alloy, they have excellent magnetic properties such as saturation magnetization. However, for purposes such as reducing eddy current loss, at least some of the magnetic grains 111 include a first layer 112 formed on the surface and a second layer 113 formed on the surface of the first layer 112. The plurality of magnetic grains 111 may have an average diameter d1 of approximately 10 to 25 μm. In this embodiment, the Fe-based alloy contained in the magnetic grains 111 may include an Fe—Si—BC-based material. More specifically, the Fe-based alloy may be free of Cr, Mo, Nb, and P. These elements are components that enhance corrosion resistance by slowing the progression of corrosion of the magnetic grains 111. However, if the content of these elements increases, the content of Fe may relatively decrease, potentially reducing the saturation magnetization of the magnetic grains 111. In this embodiment, an Fe-based alloy containing a relatively large amount of Fe is used to ensure sufficient saturation magnetization characteristics, and even in such a case, the first layer 112, which corresponds to the surface oxide film, is formed extremely thin, so that the magnetic grains 111 can exist at a sufficient volume fraction within the magnetic body 101. Details of the magnetic grains 111 and the insulating structure (first and second layers) will be described later.

[0034] In one example of a manufacturing method, the magnetic body 101 may be formed by a lamination method. Specifically, after forming the coil 103 on the support member 102 using a method such as plating, a plurality of unit laminates for manufacturing the magnetic body 101 are prepared and laminated. Here, the unit laminates may be manufactured by mixing magnetic particles 111, such as metal, with organic materials such as a thermosetting resin, binder, and solvent to prepare a slurry, and then coating the slurry on a carrier film using a doctor blade method to a thickness of several tens of micrometers and drying it to form a sheet. As a result, the unit laminates may be manufactured in a form in which magnetic particles are dispersed in a thermosetting resin, such as epoxy resin or polyimide. The magnetic particles 111 may have the shape described above, and a first layer 112 and a second layer 113 are formed on the surface. A plurality of the unit laminates described above may be formed and pressure-laminated above and below the coil 103 to realize the magnetic body 101.

[0035] The support member 102 supports the coil 103 and may be made of polypropylene glycol (PPG), ferrite, a metal-based soft magnetic material, etc. As shown in the figure, a through hole is formed through the center of the support member 102, and the magnetic material 101 is filled in the through hole to form the magnetic core part C.

[0036] The coil 103 is disposed inside the magnetic body 101 and can perform various functions within an electronic device. For example, the magnetic component 100 may be a power inductor, in which case the coil 103 may store electricity in the form of a magnetic field, maintain an output voltage, and stabilize a power supply. In this case, the coil 103 may be laminated on both sides of the support member 102 and may be electrically connected to the support member 102 through conductive vias V that penetrate the support member 102. The coil 103 may be formed in a spiral shape, and the outermost periphery of the spiral may include a lead portion T exposed to the outside of the magnetic body 101 for electrical connection with external electrodes 105 and 106.

[0037] The coil 103 is disposed on at least one of a first surface (upper surface in FIG. 2 ) and a second surface (lower surface in FIG. 2 ) that face each other of the support member 102. As in the present embodiment, a first coil 103 a and a second coil 103 b may be disposed on the first surface and the second surface of the support member 102, respectively, and in this case, the coil 103 may include a pad P. However, instead, the coil 103 may be disposed on only one surface of the support member 102. Meanwhile, the coil pattern forming the coil 103 may be formed using a plating process used in the art, such as pattern plating, anisotropic plating, isotropic plating, etc., and may also be formed in a multi-layer structure using a combination of these processes.

[0038] The external electrodes 105 and 106 may be formed outside the magnetic body 101 and connected to the lead-out portion T. The external electrodes 105 and 106 may be formed using a paste containing a metal with excellent electrical conductivity, such as a conductive paste containing nickel (Ni), copper (Cu), tin (Sn), or silver (Ag) alone or an alloy thereof. A plating layer may also be formed on the external electrodes 105 and 106. In this case, the plating layer may include at least one selected from the group consisting of nickel (Ni), copper (Cu), and tin (Sn). For example, a nickel (Ni) layer and a tin (Sn) layer may be formed sequentially. In FIG. 1, the external electrodes 105 and 106 extend from one side of the magnetic body 101 to the top and bottom surfaces and the remaining side surfaces. However, the external electrodes may have various other shapes, such as an L-shape.

[0039] To explain the multiple magnetic particles 111 contained in the magnetic body 101 in more detail, the Fe content in the Fe-based alloy contained in the magnetic particles 111 may be relatively large, for example, exceeding 90 wt%. As the Fe content in the Fe-based alloy increases, any one or none of Cr, Mo, Nb, and P may need to be added. To exemplify more specific compositional conditions, the Si content in the Fe-based alloy may be 0.1 to 5 wt%. Furthermore, the B content in the Fe-based alloy may be 0.1 to 5 wt%. Furthermore, the C content in the Fe-based alloy may be 0.1 to 2 wt%.

[0040] Meanwhile, the average diameter d1 of the magnetic particles 111 may be 10 to 25 μm, and the diameter d1 may be measured, for example, through an image of a cross section of the magnetic material 101. As a specific example, a cross section in the D1-D3 direction passing through the center of the magnetic material 101 is photographed with a scanning electron microscope at a plurality of equally spaced regions (e.g., 10 regions) in the D2 direction, and then the diameter d1 of the magnetic particles 111 can be obtained using an image analysis program. In this case, the outer region of the magnetic material 101 may be deformed or the first layer 112 and second layer 113 may be destroyed due to a compression process, so the diameter d1 of the magnetic particles 111 may be measured excluding this region. For example, a region within 5% or 10% of the length from the surface of the magnetic material 101 may be excluded.

[0041] In the case of magnetic particles 111 with enhanced saturation magnetization, the Fe-based alloy contained therein does not need to contain corrosion-resistance-enhancing elements. However, a thick oxide film may form on the surface due to reduced corrosion resistance. This oxide film corresponds to a surface oxide film or a natural oxide film formed on the surface of the magnetic particles 111. Because its structure is not dense, moisture and oxygen may continue to penetrate. This oxide film may have the form of a secondary phase of Fe oxide. If it becomes excessively thick, the magnetic properties, such as the magnetic permeability, of the magnetic material 101 may be reduced. In this embodiment, the average thickness t1 of the first layer 112, which corresponds to the surface oxide layer, is reduced to a level exceeding 0 nm and less than 5 nm, thereby reducing the proportion of the oxide layer within the magnetic particles 111 and thereby minimizing the degradation of the magnetic permeability characteristics of the magnetic particles 111. As described below, sufficient magnetic permeability can be ensured when the average thickness t1 of the first layer 112 is achieved to be thinner than 5 nm.

[0042] The first layer 112 may be formed by oxidizing the surface of the magnetic grain 111, and thus may be formed directly on the surface of the magnetic grain 111. In this case, the thickness t1 of the first layer 112 may be defined as the distance from the surface of the magnetic grain 111 to the surface of the first layer 112, and may correspond to the average thickness of thicknesses measured in multiple regions. The average thickness t1 of the first layer 112 may be obtained by obtaining an SEM or TEM image of at least one cross section of the magnetic grain 111 and then measuring the thickness in multiple equally spaced regions. The first layer 112 may include at least one of an Fe—O-based material and an Fe—Si—O-based material, for example, the first layer 112 may include Fe2O3. Unlike the second layer 113, even when the first layer 112 includes an Fe—Si—O-based material, it is preferable that an extremely small amount of Si be added; for example, the first layer 112 may include an Si component of less than 1 wt %. In addition, the first layer 112 may be formed with an amorphous structure, and therefore, when analyzing its presence or absence, it can be analyzed as a composition rather than a structure. If a thick native oxide film is formed on the surface of the magnetic grains 111, crystallization occurs during heat treatment, and the film reacts with the second layer 113 containing Si components to form a secondary phase, which may result in a decrease in magnetic permeability and withstand voltage characteristics.

[0043] FIG. 4 illustrates the reduction in thickness of the surface insulating layer of a magnetic particle. Referring to FIG. 4, the first layer 112 is initially formed as a thick layer 112' on the surface of the magnetic particle 111, and then its thickness can be reduced by a separate etching process. As described above, the surface oxide film of the thick layer 112' can be formed thicker (e.g., 20 nm or more) when the Fe-based alloy does not contain a corrosion-resistant element. However, this may adversely affect the magnetic properties of the magnetic component 100. In this embodiment, the thick layer 112' is etched to reduce its thickness, so that the average thickness t1 of the first layer 112 is less than 5 nm. As described below, when the average thickness t1 of the first layer 112 is less than 5 nm and the average thickness t2 of the second layer 113 is 5 nm or more, sufficient magnetic permeability can be ensured while maintaining excellent voltage resistance characteristics.

[0044] The second layer 113 of the multilayer insulating structure of this embodiment may be provided to ensure more stable insulating properties, and has an average thickness t2 of 5 nm or more. The upper limit of the average thickness t2 of the second layer 113 may be determined within a range in which magnetic properties such as magnetic permeability are not significantly reduced. For example, the average thickness t2 may be less than 50 nm. The thickness t2 of the second layer 113 may be defined as the distance from the surface of the first layer 112 to the surface of the second layer 113, and may correspond to an average thickness of thicknesses measured in multiple regions. The average thickness t2 of the second layer 113 may be obtained by obtaining an SEM or TEM image of at least one cross section of the magnetic grain 111 and then measuring the thickness in multiple regions at equal intervals. The average thickness t2 of the second layer 113 is thicker than the average thickness t1 of the first layer 112 and may be 2 to 10 times the average thickness t1 of the first layer 112.

[0045] The second layer 113 includes a Si oxide component, for example, SiO2. In this case, the second layer 113 may include 30 wt% to 70 wt% of the Si component. When the second layer 113 includes a Si oxide such as SiO2, the insulating properties can be further improved and the layer can have a uniform thickness. Conventionally, commonly used insulating coating materials based on Sn oxide or P oxide have problems such as low uniformity in the coating layer thickness and insufficient voltage resistance. The second layer 113 including Si oxide, as in this embodiment, can improve the insulating properties of the magnetic particles 111 and further delay the saturation magnetization. Additionally, as an additional effect, the second layer 113 has a strong bond with the insulating material 110 included in the magnetic body 101, thereby improving reliability at high temperatures and high humidity. When the average diameter d1 of the magnetic particles 111 is relatively large, at 10 to 25 μm, as in this embodiment, the second layer 113 can exhibit further improved properties such as improved voltage resistance. A liquid coating method can be used as an example of a method for forming the second layer 113. For example, a liquid coating method using TEOS (Tetraethyl orthosilicate) can be used, and the second layer 113 can be coated uniformly to a thickness of several tens of nanometers through hydrolysis using ammonia water as a catalyst.

[0046] In the above example, the thicknesses t1 and t2 of the first layer 112 and the second layer 113 were measured using SEM or TEM images. However, the thicknesses can also be obtained through TEM-EDS analysis. Specifically, after polishing a sample of the magnetic component 100, the cross section of the magnetic grains 111 present in the magnetic material 101 was observed using an SEM. A sample near the surface of the magnetic grains 111 was collected using a focused ion beam (FIB). The magnetic grains 111 and their surface insulating structures were observed using a STEM with a magnification of 110K or more and an acceleration voltage of 200 kV. The magnetic grains and their surface insulating structures were observed using a STEM with a magnification of 110K or more and an acceleration voltage of 200 kV. This allowed an EDS line profile scan from near the surface of the magnetic grains 111 to the insulating structures (first and second layers), and the first layer 112 could be defined as the region from where the Fe content rapidly decreases to where the Si content rapidly increases. The second layer 113 can be defined as the region from the portion where the Si component increases abruptly to the portion where the Si component decreases abruptly.

[0047] The inventors of the present invention manufactured samples with different average thicknesses t1 and t2 of the first and second layers 112 and 113, and measured the magnetic permeability and withstand voltage characteristics for these samples. The magnetic permeability and withstand voltage characteristics were measured by preparing powder cores, and the magnetic permeability was converted according to the powder particle size to provide a standard for determining whether or not the sample was defective. For withstand voltage characteristics, samples with a breakdown voltage of 100 V / mm or more were marked with "O," and samples with a breakdown voltage of less than 100 V / mm were marked with "X."

[0048] [Table 1]

[0049] According to the above experimental results, when the average thickness t1 of the first layer 112 is less than 5 nm and the average thickness t2 of the second layer 113 is 5 nm or more, it is possible to obtain sufficient magnetic permeability while also satisfying the voltage resistance characteristics.

[0050] The modified examples shown in FIGS. 5 and 6 will now be described. First, in the modified example of FIG. 5, an additional coating layer is formed on the surface of the magnetic particle 111. Specifically, the magnetic particle 111 may further include a third layer 114 formed on the surface of the second layer 113, where the third layer 114 may be a surface treatment layer obtained by surface-treating the second layer 113. The third layer 114 in the form of a surface treatment layer allows the magnetic particle 111 to have a hydrophobic surface, thereby increasing the bonding strength between the magnetic substance 101 and the insulating material 110 and improving the reliability of the magnetic component 100. It is preferable to use a material that has excellent bonding strength with the second layer 113 and the insulating material 110 as the surface treatment agent for the second layer 113 of the magnetic particle 111. For example, at least one of oleic acid and a silane coupling agent may be used. Here, the silane coupling agent may be a urethane silane coupling agent.

[0051] The third layer 114 may include at least one functional group selected from the group consisting of an alkyl group, a carbonyl group, and a urethane acrylate. The functional group included in the third layer 123 may be detected using Fourier-transform infrared (FT-IR) spectroscopy. When the third layer 114 is a surface treatment layer, the magnetic material 101 may include at least one component selected from the group consisting of oleic acid, an oleic acid derivative, and carbonic acid monoamide N-allyl neopentyl ester. The oleic acid derivative may include at least one component selected from the group consisting of oleic acid methyl ester, butyl oleate, and oleic acid 3-hydroxypropyl ester. The above components contained in magnetic body 101 can be detected by gas chromatography-mass spectrometry (GC-MS). As described above, third layer 114 functions to improve the bonding strength with insulating material 110 within magnetic body 101, but if it becomes too thick, the magnetic permeability of magnetic body 101 may decrease, so its average thickness t3 can be less than 10 nm.

[0052] Next, in the modified example of FIG. 6, the magnetic body 101 has a configuration in which relatively small magnetic particles 121 are added, thereby increasing the packing ratio of the magnetic particles 111, 121 within the magnetic body 101. Specifically, the magnetic body 101 may further include additional magnetic particles 121 having an average diameter d2 smaller than that of the magnetic particles 111 comprising the first layer 112 and the second layer 113. The additional magnetic particles 121 fill the spaces between the magnetic particles 111, thereby increasing the total amount of the magnetic particles 111, 121 present within the magnetic body 101. In this case, the average diameter d2 of the additional magnetic particles 121 may be 5 μm or less. The additional magnetic particles 121 may be made of pure iron, for example, in the form of carbonyl iron particles (CIP, Carbonyl Iron Powder). In this case, a coating layer comprising the first layer 112 and the second layer 113 may not be formed on the surface of the additional magnetic particles 121.

[0053] Another embodiment of the present invention will be described with reference to FIGS. 7 to 9. In the above-described embodiment, the coil 103 and the support member 102 supporting the coil 103 are disposed within the magnetic body 101. The embodiment of FIGS. 7 to 9 differs from this in that a wire-wound coil is used. Specifically, the magnetic component 200 includes a molded portion 250, a coil 230, a cover portion 211, and receiving grooves h1 and h2, as well as external electrodes 270 and 280. The magnetic body forms the exterior of the magnetic component 200 and has the coil 230 embedded therein. The magnetic body includes the molded portion 250 and the cover portion 211. The molded portion 250 may include a core 220. The magnetic body may be formed into a hexahedron shape as a whole. The magnetic body includes a first surface 201 and a second surface 202 facing a first direction D1, a third surface 203 and a fourth surface 204 facing a second direction D2, and a fifth surface 205 and a sixth surface 206 facing a third direction D3. The third to sixth surfaces 203 to 206 of the magnetic body correspond to wall surfaces of the magnetic body that connect the first surface 201 and the second surface 202 of the magnetic body, respectively.

[0054] For example, the magnetic body may be formed such that the magnetic component 200 according to this embodiment, including the external electrodes 270 and 280 described below, has a length of 2.0 mm, a width of 1.2 mm, and a thickness of 0.6 mm, but is not limited thereto. The magnetic body includes a molded part 250 and a cover part 211. The cover part 211 is disposed on the upper part of the molded part 250 and surrounds all surfaces of the molded part 250 except for the lower surface. The molded part 250 has one and other opposing surfaces. The one surface of the molded part 250 corresponds to the lower surface of the molded part 250 and refers to an area where the receiving grooves h1 and h2 described below are disposed. As described below, the receiving grooves h1 and h2 are machined inside the molded part 250, and therefore, the bottom surfaces of the receiving grooves h1 and h2 may be disposed in an area between the one and other surfaces of the molded part 250. The molded part 250 includes a support part 210 and a core 220. The core 220 is disposed at the center of the other surface of the support part 210 in a manner that penetrates the coil 230. The mold part 250 may be formed by filling a composite material including magnetic particles 111 and insulating resin into a mold. Here, the insulating resin may include, but is not limited to, epoxy, polyimide, liquid crystal polymer, etc., alone or in combination.

[0055] The coil 230 is embedded in a magnetic material and exhibits the characteristics of the magnetic component 200. For example, when the magnetic component 200 of this embodiment is used as a power inductor, the coil 230 can stabilize the power supply of an electronic device by storing an electric field as a magnetic field and maintaining an output voltage. The coil 230 is disposed on the other side of the molded part 250. Specifically, the coil 230 is wound around the core 220 and disposed on the other side of the support part 210. The coil 230 is an air-core coil and may be formed as a rectangular coil. The coil 230 may be formed by spirally winding a metal wire, such as a copper wire, whose surface is coated with an insulating material. The coil 230 may be formed of multiple layers. Each layer of the coil 230 may be formed in a planar spiral shape and have multiple turns. That is, the coil 230 may be formed from the center of one side of the molded part 250 to the outside, with an innermost turn T1, at least one middle turn T2, and an outermost turn T3.

[0056] The cover part 211 may be disposed on the mold part 250 and the coil 230. The cover part 211 covers the mold part 250 and the coil 230. After being disposed on the support part 210, the core 220, and the coil 230 of the mold part 250, the cover part 211 may be pressed and bonded to the mold part 250. The mold part 250 and the cover part 211 each include magnetic particles 111, where the magnetic particles 111 may include the first layer 112 and the second layer 113 formed on the surface as described above.

[0057] The first and second accommodating grooves h1 and h2 are formed on one surface of the molded part 250 and spaced apart from each other, and both ends of the coil 230 (described later) are disposed in the first and second accommodating grooves h1 and h2. For example, the first and second accommodating grooves h1 and h2 are formed on one surface of the molded part 250 and spaced apart from each other along the longitudinal direction X. The first and second accommodating grooves h1 and h2 may be disposed outside an area of ​​the one surface of the molded part 250 that corresponds to the core 220, but are not limited thereto. The first and second accommodating grooves h1 and h2 may be formed to extend in one direction on one surface of the molded part 250, but may be formed in any shape that can effectively expose both ends of the coil 230.

[0058] Since the magnetic body is an area including the molded part 250 and the cover part 211, one side of the magnetic body refers to one side of the area including the molded part 250 and the cover part 211. The coil 230 is drawn out to the outside and includes a first lead-out portion and a second lead-out portion disposed in the first accommodating groove h1 and the second accommodating groove h2, respectively. The first accommodating groove h1 and the second accommodating groove h2 are areas that draw both ends of the coil 230 to the external electrodes 270 and 280, and therefore are formed on one side of the magnetic body, spaced apart from each other, to correspond to the first external electrode 270 and the second external electrode 280, respectively.

[0059] For example, the through grooves H1 and H2 may be formed by a mold when the molded part 250 is formed, and the first and second accommodating grooves h1 and h2 may be formed in the molded part 250 during the process of forming the cover part 211 by stacking and pressing a magnetic sheet containing metal magnetic particles. The mold for forming the molded part 250 may have protrusions corresponding to the through grooves H1 and H2, and the through grooves H1 and H2 may be formed in the molded part 250, which is manufactured in a shape corresponding to the shape of the mold. Furthermore, the first and second accommodating grooves h1 and h2 may be formed during the process of forming the cover part 211 on the molded part 250, rather than during the process of forming the molded part 250. That is, both ends of the coil part 230 protruding from one side of the molded part 250 through the through grooves H1 and H2 of the molded part 250 may be embedded inside the molded part 250 during the process of pressing the magnetic sheet. As a result, the first accommodating groove h1 and the second accommodating groove h2 may be formed on one surface of the molded part 250. Alternatively, the first accommodating groove h1 and the second accommodating groove h2 and the through grooves H1 and H2 may be formed in a process of forming the molded part 250 using a mold. In this case, the mold used to form the molded part 250 may have protrusions formed therein corresponding to the first accommodating groove h1 and the second accommodating groove h2 and the through grooves H1 and H2.

[0060] Both ends of the coil 230 may penetrate one surface of the molded part 250 and be disposed in the first accommodating groove h1 and the second accommodating groove h2, respectively. The manner in which the ends of the coil 230 are disposed in the accommodating grooves h1 and h2 is not limited, and the widths of the first accommodating groove h1 and the second accommodating groove h2 may be the same as or different from the widths of the through-grooves H1 and H2. Both ends of the coil 230 are exposed to one surface of the molded part 250, i.e., the second surface 202 of the magnetic body. The both ends of the coil 230 exposed to one surface of the molded part 250 are disposed in the first accommodating groove h1 and the second accommodating groove h2, which are spaced apart from each other in the second surface 202 of the magnetic body. Both ends of the coil 230 may penetrate the support part 210 of the molded part 250 and be exposed to one surface of the support part 210. Although not specifically shown, both ends of the coil 230 have the same thickness as the coil 230, and therefore may protrude from one surface of the support part 210 by an amount corresponding to the thickness of the coil 230. However, since the protruding ends may also be polished during the process of polishing openings in a plating resist for forming the external electrodes 270 and 280, which will be described later, the ends of the coil 230 exposed on one surface of the support part 210 may be substantially smaller than the thickness of the coil 230.

[0061] The external electrodes 270, 280 may be spaced apart from each other on one surface of the magnetic body, i.e., the second surface 202. Specifically, the external electrodes 270, 280 may be spaced apart from each other on one surface of the molded part 250 and connected to both ends of the coil 230 disposed in the first receiving groove h1 and the second receiving groove h2, respectively. Both ends of the coil 230 are disposed along the bottom surfaces of the first receiving groove h1 and the second receiving groove h2, and the external electrodes 270, 280 are applied along both ends of the coil 230, so that the external electrodes may be formed to correspond to the shapes of the first receiving groove h1 and the second receiving groove h2. For example, the external electrodes 270, 280 may be formed by applying a conductive resin containing a conductive powder such as silver (Ag) onto the first receiving groove h1 and the second receiving groove h2. The external electrodes 270, 280 may be formed from a conductive material such as, but not limited to, copper (Cu), aluminum (Al), silver (Ag), tin (Sn), gold (Au), nickel (Ni), lead (Pb), chromium (Cr), titanium (Ti), or an alloy thereof, and may be formed in a single-layer or multi-layer structure.

[0062] Meanwhile, the magnetic component 200 according to this embodiment may further include an insulating layer 290 surrounding the surface of the coil 230. There is no limitation on the method for forming the insulating layer 290. For example, the insulating layer 290 may be formed by chemical vapor deposition of a parylene resin or the like on the surface of the coil 230, or may be formed by a known method such as a screen printing method, a photoresist (PR) exposure and development process, spray coating, or dipping process. There is no particular limitation on the insulating layer 290 as long as it can be formed into a thin film. For example, the insulating layer 290 may be formed using a photoresist (PR), an epoxy-based resin, or the like.

[0063] The present invention is not limited by the above-described embodiments and the accompanying drawings, but is limited by the appended claims. Therefore, various substitutions, modifications, and changes may be made by a person skilled in the art within the scope of the technical idea of ​​the present invention as set forth in the claims, and these also fall within the scope of the present invention. [Explanation of symbols]

[0064] 100 Magnetic parts 101 Magnetic materials 102 Support member 103 Coil 110 Insulation material 111, 121 magnetic particles 112 1st layer 113 2nd layer 114 3rd layer C Core L Drawer part P Pad V Conductive Via

Claims

1. In a magnetic component including a magnetic body, the magnetic body includes a plurality of magnetic particles including an Fe-based alloy component; At least some of the magnetic particles include a first layer formed on a surface and a second layer formed on a surface of the first layer, the first layer comprises an Fe oxide component and has an average thickness of less than 5 nm; The second layer comprises a Si oxide component and has an average thickness of 5 nm or more.

2. The magnetic component according to claim 1 , wherein the first layer contains a Si component of less than 1% by weight.

3. 3. The magnetic component according to claim 2, wherein the second layer contains 30% by weight to 70% by weight of Si.

4. The magnetic component of claim 1 , wherein the second layer has an average thickness of less than 50 nm.

5. 2. The magnetic component according to claim 1, wherein the average thickness of the second layer is 2 to 10 times the average thickness of the first layer.

6. 2. The magnetic component according to claim 1, wherein the average diameter of the magnetic particles is 10 to 25 μm.

7. The magnetic component of claim 1 , wherein the at least some of the magnetic particles further include a third layer formed on a surface of the second layer.

8. The magnetic component of claim 7 , wherein the third layer includes at least one functional group selected from the group consisting of an alkyl group, a carbonyl group, and a urethane acrylate.

9. 8. The magnetic component of claim 7, wherein the magnetic material includes at least one component selected from the group consisting of oleic acid, derivatives of oleic acid, and carbonic acid monoamide n-allyl neopentyl ester.

10. The magnetic component of claim 7 , wherein the third layer has an average thickness of less than 10 nm.

11. The magnetic component of claim 1 , wherein the Fe-based alloy comprises a Fe—Si-B—C material.

12. The magnetic component according to claim 11 , wherein the Fe-based alloy does not contain Cr, Mo, Nb, or P components.

13. The magnetic component according to claim 11 , wherein in the Fe-based alloy, the Fe content is more than 90 wt %.

14. The magnetic component according to claim 13, wherein the Fe-based alloy has a Si content of 0.1 to 5 wt %.

15. 15. The magnetic component of claim 1, wherein the magnetic body further comprises additional magnetic grains having a smaller average diameter than the magnetic grains comprising the first and second layers.

16. 16. The magnetic component of claim 15, wherein the additional magnetic particles include carbonyl iron powder.